Genetic associations between flight speed and growth traits in Nellore cattle - Sant'Anna, A. C. [UNESP]; Paranhos da Costa, M. J. R. [UNESP]; Baldi, Fernando [UNESP]; Baldi, Fernando [UNESP]; Rueda, P. M. [UNESP]; Albuquerque, Lucia Galvão de [UNESP] (Amer Soc Animal Science, 2012)
The aim of the present study was to estimate genetic parameters for flight speed and its association with growth traits in Nellore beef cattle. The flight speed (FS) of 7,402 yearling animals was measured, using a device composed of a pair of photoelectric cells. Time interval data (s) were converted to speed (m/s) and faster animals were regarded as more reactive. The growth traits analyzed were weaning weight (WW), ADG from weaning to yearling age, and yearling scrotal circumference (SC). The (co)variance components were estimated using REML in a multitrait analysis applying an animal model. The model included random direct additive genetic and residual effects, fixed effects of contemporary groups, age of dam (classes), and age of animal as covariable. For WW, the model also included maternal genetic and permanent environmental random effects. The direct heritability estimate for FS was 0.26 +/- 0.05 and direct heritability estimates for WW, SC, and ADG were 0.30 +/- 0.01, 0.48 +/- 0.02, and 0.19 +/- 0.01, respectively. Estimates of the genetic correlation between FS and the growth traits were -0.12 +/- 0.07 (WW), -0.13 +/- 0.08 (ADG), and -0.11 +/- 0.07 (SC). Although the values were low, these correlations showed that animals with better temperaments (slower FS) tended to present better performance. It is possible to infer that long-term selection for weight and scrotal circumference can promote a positive genetic response in the temperament of animals. Nevertheless, to obtain faster genetic progress in temperament, it would be necessary to perform direct selection for such trait. Flight speed is an easily measured indicator of temperament and can be included as a selection criterion in breeding programs for Nellore cattle.
Keywords: average daily gain; Genetic correlation; Heritability; scrotal circumference; Temperament